A checklist of the plants of Mahwaqa Mountain, KwaZulu-Natal - E. B. Meter (Bothalia: African Biodiversity & Conservation, 2002)
A checklist o f the plants of Mahwaqa Mountain. KwaZulu-Natal, is presented. The list includes 1 030 indigenous and naturalized flowering plants and ferns. Comparisons are made with the floras of KwaZulu-Natal (Ross 1972). the Cape of Good Hope Nature Reserve, Cape Point (Taylor 1985). the southern Natal Drakensberg (Hilliard & Burtt 1987). the Amatolas (Phillipson 1987). the Langeberg (McDonald 19991  and Umtamvuna Nature Reserve (Abbott  et al. 2000). It is hoped that the publication of this list w ill contribute towards the recognition of the area as a natural heritage site.